2004
DOI: 10.1182/blood-2003-07-2187
|View full text |Cite
|
Sign up to set email alerts
|

Receptor synergy of interleukin-6 (IL-6) and insulin-like growth factor-I in myeloma cells that highly express IL-6 receptor α

Abstract: Interleukin-6 (IL-6) is a growth and antiapoptotic factor for human myeloma cells. The autocrine loop and increased expression of the growth factor receptors have been postulated as the mechanisms of tumorigenesis. Here we show that IL-6 stimulation induced the phosphorylation of insulin-like growth factor-I (IGF-I) receptors in a human myeloma cell line, NOP2, highly expressing IL-6 receptor ␣ (IL-6R␣) and in the IL-6R␣-transfected U266 cell line. IL-6-dependent complex formation of IL-6R␣ with IGF-I receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 53 publications
(55 reference statements)
0
48
1
Order By: Relevance
“…These data are in agreement with previous work by Jeon et al (2010), who demonstrated that galectin-3 may exert its functions primarily through the JAK-STAT pathway. Together, our results indicate that galectin-3 deficiency leads to a defective microglia activation and defective IGF-R1 signaling/mitogenic response in microglial cells, and likely compensatory overexpression of IL-6 (Abroun et al, 2004). This may lead to an overactivation of JAK/STAT pathway and upregulation of a feedback inhibitor SOCS3 (Wormald et al, 2006).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These data are in agreement with previous work by Jeon et al (2010), who demonstrated that galectin-3 may exert its functions primarily through the JAK-STAT pathway. Together, our results indicate that galectin-3 deficiency leads to a defective microglia activation and defective IGF-R1 signaling/mitogenic response in microglial cells, and likely compensatory overexpression of IL-6 (Abroun et al, 2004). This may lead to an overactivation of JAK/STAT pathway and upregulation of a feedback inhibitor SOCS3 (Wormald et al, 2006).…”
Section: Discussionmentioning
confidence: 82%
“…7A-C) (***p Ͻ 0.0001). Since growing evidence suggests a crosstalk and synergy between IL-6 and IGF-R1, we further analyzed downstream IGFR1-mediated signaling events (Abroun et al, 2004;Sprynski et al, 2009).…”
Section: Galectin-3 Deficiency Leads To Overexpression Of Il-6 and Inmentioning
confidence: 99%
“…Obesity is also associated with insulin resistance and other metabolic disorders that can result indirectly in the modulation of bioavailable insulin-like growth factor-I (27)(28)(29), another important growth and survival factor in multiple myeloma (30)(31)(32). Furthermore, synergy in the IL-6 and insulin-like growth factor-I pathways has been suggested by in vitro experiments on multiple myeloma cell lines (33). Thus, although BMI does not seem to correlate directly with circulating levels of insulin-like growth factor-I (29), obesityrelated increases in bioavailable insulin-like growth factor-I may further contribute to multiple myeloma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…First strand DNA was synthesized with fgfr3-RT, and either fgfr3-U or fgfr3-1 as sense primers and fgfr3-D as an antisense primer amplified the full-length fgfr3 cDNA. After confirming the nucleotide sequence of the fragments, they were transferred into the retroviral vector pRep (pMxpuro, Onishi et al, 1998) followed by retrovirus infection into U266 myeloma cell line as reported previously (Abroun et al, 2004). Sequences of the primers were as follows: fgfr3-RT: 5 0 -TGCACCAGCAGCAGGGAGGGCTGCTA-3 0 , fgfr3-U: 5 0 -CGCGCGCTGCCTGAGGACGCCG-3 0 , fgfr3-1: 5 0 -CGGCCCCCGCCCCCGCCATG-3 0 , fgfr3-D: 5 0 -TGGGGACCAGTGGCC CTTCACGTCCG-3 0 .…”
mentioning
confidence: 99%